2017
DOI: 10.1038/s41598-017-13870-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation regulates the subcellular localization of Cucumber Mosaic Virus 2b protein

Abstract: The 2b protein of Cucumber mosaic virus has a role in nearly all steps of the viral cycle including cell-to-cell movement, symptom induction and suppression of antiviral RNA silencing. Previous studies demonstrated the presence of 2b protein in the nucleus and in cytoplasm as well. Phosphorylation site of 2b protein is conserved in all CMV isolates, including proposed constitute motifs for casein kinase II and cyclin-dependent kinase 2. To discern the impact of 2b protein phosphorylation, we created eight diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…The two nuclear localization sequence domains of the 2b protein sequence are conserved among CMV subgroup IA strains and are required for entry of the protein into the nucleus and for RNA silencing suppressor activity (Du et al , ; González et al , , ; Goto et al ., ; Mayers et al , ; Wang et al , ). The KSPSE protein domain (comprising the amino acid residues lysine‐serine‐proline‐serine‐glutamic acid) can be reversibly phosphorylated and is required for shuttling of the 2b protein between the nuclear and cytoplasmic compartments of the cell (Lewsey et al , ; Nemes et al , ). Deletion of this sequence results in a 2b protein variant that appears to be trapped in the nucleolus (González et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The two nuclear localization sequence domains of the 2b protein sequence are conserved among CMV subgroup IA strains and are required for entry of the protein into the nucleus and for RNA silencing suppressor activity (Du et al , ; González et al , , ; Goto et al ., ; Mayers et al , ; Wang et al , ). The KSPSE protein domain (comprising the amino acid residues lysine‐serine‐proline‐serine‐glutamic acid) can be reversibly phosphorylated and is required for shuttling of the 2b protein between the nuclear and cytoplasmic compartments of the cell (Lewsey et al , ; Nemes et al , ). Deletion of this sequence results in a 2b protein variant that appears to be trapped in the nucleolus (González et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of a putative phosphorylation sequence or the mutation of two serine sites within this sequence in CMV 2b greatly weakened CMV‐induced symptoms (Lucy et al ., ). A recent study showed that the phosphorylation of CMV 2b regulated its subcellular localization to influence the VSR activity of 2b protein (Nemes et al ., ). Using LC‐MS/MS, we showed that the Ser‐96 site in γb is phosphorylated by a PKA‐like protein kinase and found that its phosphorylation is related to BSMV induced symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…As several suppressor proteins have multiple roles, including non-silencing functions critical for virus viability, and their synchronized action is essential in order to fulfill the multiple tasks, post translational modification could be an efficient strategy to reach this goal. In fact, S-acylation and/or N-myristoylation is predicted in AC4/C4 of the Geminiviridae species ( S2 Table ), and phosphorylation, another mechanisms of post-translational modification, has been recently reported to regulate subcellular localization and in turn VSR activity of cucumber mosaic virus 2b protein [ 58 ]. Therefore, post-translational modification and its correlation to VSR function should be considered and investigated, particularly for those proteins with multifunctional behavior and potential localization to membrane compartment.…”
Section: Discussionmentioning
confidence: 99%